Variable Features of Juvenile Polyposis Syndrome With Gastric Involvement Among Patients With a Large Genomic Deletion of BMPR1A. Issue 7 (July 2019) - Lieberman, Sari; Beeri, Rachel; Walsh, Tom; Schechter, Menachem; Keret, Dan; Half, Elizabet; Gulsuner, Suleyman; Tomer, Ariela; Jacob, Harold; Cohen, Shlomi; Basel-Salmon, Lina; Mansur, Mahmud; et al.
Abstract : OBJECTIVES: Loss-of-function mutations of BMPR1A cause juvenile polyposis syndrome (JPS), but large genomic deletions in BMPR1A are rare, reported in few families only, and data regarding the associated phenotype are limited. METHODS: We investigated clinical features and genomic data of 7 extended seemingly unrelated families with a genomic deletion of the entire coding region of BMPR1A . We defined mutation size, mutation prevalence, and tumor pathogenesis using whole-genome sequencing, targeted genotyping, and haplotype analysis. RESULTS: Patients with JPS from 7 families of Bukharin Jewish ancestry carried a deletion of 429 kb, encompassing the BMPR1A coding sequence and 8 downstream genes. Haplotype analysis and testing controls identified this as a common founder mutation occurring in 1/124 individuals of Bukharin origin. Tumor testing did not demonstrate loss of heterozygosity. Among carriers, JPS was almost fully penetrant, but clinical features varied widely, ranging from mild to very severe, including pan-enteric polyps, gastritis, and colorectal, esophageal, and testicular cancer, and carriers with phenotypes, which would not have raised suspicion of JPS. DISCUSSION: The phenotype in this large cohort was extremely variable, although all carriers shared the same variant and the same genetic background. New observations include a preponderance of adenomatous rather than juvenile polyps, possible association with testicular cancer, and unexpected upper gastrointestinal involvement.